Utilization of Fabric Waste into Bag Products by Using Smocking Techniques - Kharisma Nisa Yunitria Wihartini (PT Publikasiku Academic Solution, 2024)
The textile industry is a supplier of clothing needs of modern society today. As a supplier of basic necessities, the textile industry is required to produce goods that are in accordance with market interests and trends circulating among the public, this rapidly developing trend that causes high waste generated by the textile industry. Waste can come from the textile industry on a small scale or on a large scale. The existence of the concept of fast fashion worsens the environment, because the concept of fast fashion changes trends quickly and in a short time, as well as the use of poor raw materials so that clothes are not durable. This has made a drastic increase in fabric waste, both the fabric waste comes from the production process of the textile industry, as well as the rest of production goods that are not sold and have changed trends. Observing trends that are circulating in the community with resets, making observations about the use of fabric waste in the textile industry with literature studies and making observations about bag craftsmen with surveys on several bag craftsmen. In addition, the exploration of techniques that must be carried out by that will determine the results of the study. The conclusion that can be drawn from this study is the Utilization of Fabric Waste into Bag Products Using Smocking Techniques can be realized. The final result of this research is a product. The product is made using patchwork waste and uses fabric manipulation techniques, can be applied well and has an aesthetic appearance